PENERAPAN MODEL PBL BERBASIS PERMAINAN EDUKASI TENTANG IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS V UPTD SD INPRES OEPURA 2 - Una Maria Fallo; Maxsel koro; Netty E. A. Nawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Thesis by Una Maria Fallo, Student ID 2101140032, Elementary School Teacher Education Study Program, Year 2025, entitled “The Implementation of Problem Based Learning Model Based on Educational Games in IPAS to Improve the Learning Outcomes of Fifth Grade Students at UPTD SD Inpres Oepura 2”.This study aims to improve students’ learning outcomes through the implementation of the Problem Based Learning (PBL) model based on educational games in the subject of Natural and Social Sciences (IPAS) in fifth grade at UPTD SD Inpres Oepura 2. The main problem faced was the low student achievement caused by uninteresting and teacher-centered learning. The research method used was Classroom Action Research (CAR) conducted in two cycles. The research subjects were 21 fifth-grade students. The research instruments included learning achievement tests, teacher and student activity observation sheets, and documentation. The results showed that students’ learning outcomes improved after the implementation of PBL based on the “Snakes and Ladders” educational game. In the pre-cycle, students’ mastery learning was only 28 ,57% After the first cycle, mastery learning increased to 38,09%, and in the second cycle, it reached 90,47% Teacher and student activities also improved in each cycle, showing active involvement in the learning process. Thus, it can be concluded that the implementation of the PBL model based on educational games is effective in improving the IPAS learning outcomes of fifth-grade students at SD Inpres Oepura 2. This study recommends that teachers use problem-based learning with educational games as an alternative strategy to create a more interactive, enjoyable, and meaningful learning environment.